Genetic Evaluation of Agronomic Traits in Early-maturing White Maize under Savannah Agroecologies - Bello, Bashir Omolaran; Shuaibu, Musa; Azeez, Alafe Hakeem; Abidoye, Zainab Adeola (Journal of Nepal Agricultural Research Council, 2025)
Understanding genetic variability in maize is critical for identifying traits that enhance breeding efficiency, particularly in drought-prone environments. This study evaluated genetic variance, heritability, and genetic advance for grain yield and associated agronomic traits in early-maturing white maize cultivars. Eighteen cultivars obtained from the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria, were assessed during the 2023 and 2024 cropping seasons at the Lower Niger River Basin Development Authority, Oke-Oyi, Nigeria, using a randomized complete block design with three replications. Data on grain yield, plant height, days to silking, and other key traits were subjected to analysis of variance, and estimated of phenotypic and genotypic variance, phenotypic and genotypic coefficients of variation, broad-sense heritability, and genetic advance were computed to guide selection strategies. Across all traits, phenotypic coefficients of variation exceeded genotypic coefficients of variation (GCVs), indicating a significant environmental influence. Traits including number of grains per ear, grain yield, plant height, and days to silking exhibited high GCV, high heritability, and high genetic advance, indicating substantial potential for improvement through selection. Six cultivars, 2013 DTE STR-W SYN F₁, 2012 TZE-W POP DT C₄ STR C₅, EV DT-W 2000 STR, 2011 TZE-W DT STR SYN, 2009 DTE-W STR, and 2008 DTMA-W STR, demonstrated superior grain yield performance. These findings underscored the value of genetic variance, heritability, and genetic advance as tools for guiding maize improvement programs. The identified high-yielding cultivars were recommended for multi-location and on-farm trials to validate their performance and adaptability under drought-prone savannah agroecologies.